Inhibitors of DNA Methyltransferases From Natural Sources: A Computational Perspective - Saldívar-González, Fernanda I.; Gómez-García, Alejandro; Chávez-Ponce de León, David E.; Sánchez-Cruz, Norberto; Ruiz-Rios, Javier; Pilón-Jiménez, B. Angélica; Medina-Franco, José L. (Frontiers in Pharmacology, 2018)
Naturally occurring small molecules include a large variety of natural products from different sources that have confirmed activity against epigenetic targets. In this work we review chemoinformatic, molecular modeling, and other computational approaches that have been used to uncover natural products as inhibitors of DNA methyltransferases, a major family of epigenetic targets with therapeutic interest. Examples of computational approaches surveyed in this work are docking, similarity-based virtual screening, and pharmacophore modeling. It is also discussed the chemoinformatic-guided exploration of the chemical space of naturally occurring compounds as epigenetic modulators which may have significant implications in epigenetic drug discovery and nutriepigenetics.